Associations Between Anemia, Cognitive Impairment, and All-Cause Mortality in Oldest-Old Adults: A Prospective Population-Based Cohort Study - Wangping, Jia; Ke, Han; Shengshu, Wang; Yang, Song; Shanshan, Yang; Wenzhe, Cao; Yao, He; Miao, Liu (Frontiers in Medicine, 2021)
Abstract Objective: To evaluate the combined effects of anemia and cognitive function on the risk of all-cause mortality in oldest-old individuals. Design: Prospective population-based cohort study. Setting and Participants: We included 1212 oldest-old individuals (men, 416; mean age, 93.3 years) Methods: Blood tests, health examinations, and questionnaire survey were conducted at baseline in 2012. Mortality was assessed in the subsequent 2014 and 2018 survey waves. Cox proportional hazards models were used to evaluate anemia, cognitive impairment, and mortality risk. We used restricted cubic splines to analyze and visualize the association between hemoglobin (Hb) levels and mortality risk. Results: A total of 801 (66.1%) deaths were identified during the 6-year follow-up. We noted a significant association between anemia and mortality [hazard ratio (HR)=1.32, 95% confidence interval (CI) 1.14-1.54] after adjustinjg for confounding variables. We also observed a dose-response relationship between the severity of anemia and mortality (P<0.001). In the restricted cubic spline models, Hb levels had a reverse J-shaped association with mortality risk (HR 0.88, 95%CI 0.84-0.93 per 10 g/L-increase in Hb levels below 130 g/L). The reverse J-shaped association persisted in individuals without cognitive impairment (HR 0.88, 95%CI 0.79-0.98 per 10 g/L-increase in Hb levels below 110 g/L). For people with cognitive impairment, Hb levels were inversely associated with mortality risk (HR 0.83, 95%CI 0.78-0.89 per 10 g/L-increase in Hb levels below 150 g/L). People with anemia and cognitive impairment had the highest risk of mortality (HR 2.60, 95% CI 2.06-3.27). Conclusions: Our results indicate that anemia is associated with an increased risk of mortality in oldest-old people. Cognitive impairment modifies the association between Hb levels and mortality.